Merger incentives of cost asymmetric firms under production differentiation - Li, Xia (Kansas State University, 2012)
This report examines merger incentives of cost asymmetric firms under product differentiation and their welfare implications. Considering a simple contract under which merger profit is distributed according to the proportions of differential marginal costs between duopolistic firms, we show in a stylized model that for almost all parameter ranges (in terms of market competition intensity and marginal cost differential), a low-cost firm may have no incentive to merge with a high-cost firm whereas the high-cost firm always finds merger to be profitable. Only when marginal cost differential is sufficiently low and the degree of product similarity is sufficiently high will both the low-cost firm and the high-cost firm share the common interest in merger. On the other hand, the merger equilibrium is not welfare-improving, regardless of whether the firms initially compete in quantities or prices. Viewed from the perspective of production efficiency, mergers with differentiated products thus create a fundamental conflict between the maximization of consumer and social welfare and the maximization of firm profits. We also examine the scenario that merger takes place when merger profit exceeds the sum of firm profits under duopoly, without considering how merger profit is distributed between the firms. We discuss the conditions under which mergers may or may not be welfare-improving.
Keywords: Horizontal merger; Merger incentive; Welfare effect; Differentiated products; Implications for antitrust policy; Economics (0501)